The Role of Participatory Budgeting in Forming an Ecosystem of Civic Participation in State and Municipal Governance - Vladimir V. Vagin; Ekaterina S. Shugrina (Финансовый журнал, 2021)
The purpose of the article is to substantiate the ecosystem approach as a basis for building a model of citizen participation in state and municipal governance, manifested in the laws of the Russian Federation, strategic planning documents, and other regulations, as well as in participatory practices of budget decisions. The ecosystem of citizen participation in governance is an urgent need for the modern stage of development of civil society and the entire complex of state–civil relations in Russia. The creation of such an ecosystem can increase the efficiency of state and municipal governance, include citizens and civil society institutions in the process of selecting priorities for the actions of public authorities, and reduce the protest potential caused by the lack of a comprehensive toolkit for citizen participation in governance. Among the first steps toward the formation of this ecosystem is the development of a federal law on public participation in governance. This law should become the basis for the inclusion in sectoral legislation of provisions governing relations between public authorities and citizens directly involved in decision-making on state and municipal governance issues. An important role in the deployment of the ecosystem is played by the development and implementation of a set of measures aimed at including the issues of citizen participation in the activities of state programs and national projects of the Russian Federation, implemented at all levels of public authority. The article also defines the basic principles of the development of the civic participation ecosystem.